Diesel oxidation catalyst and method for producing same
By adopting multiple heat treatments and PGM load distribution methods in the manufacturing process of diesel oxidation catalysts, the problem of high exothermic temperature in the prior art is solved, and stable NO oxidation performance and efficient exothermic production are achieved.
Patent Information
- Application Number
- CN202380049134.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-14
AI Technical Summary
The existing diesel oxidation catalysts have a higher temperature when exothermic heat generation, resulting in a lower possibility of the engine operating above the exothermic temperature, and more energy is required to achieve the appropriate operating temperature, affecting efficiency and performance.
In the process of manufacturing the diesel oxidation catalyst, a method of multiple heat treatments, including the first heat treatment to at least 600°C and maintaining a certain period of time, and the second heat treatment to a lower temperature, is used to stabilize the NO oxidation activity and in the catalyst. The front provides high PGM loading to improve heat generation capacity.
It achieves stable NO oxidation performance at lower exothermic generation temperatures, reduces dependence on engine management, and improves the overall performance and life of the catalyst.
Smart Images

Figure CN119451745A_ABST
Abstract
Description
[0001] The present invention relates to an improved diesel oxidation catalyst (DOC), and in particular to a method for making the DOC. The manufacturing method provides a DOC having stable NO to NO2 oxidation performance without compromising CO / HC oxidation performance and / or exothermic generation capability.
[0002] Internal combustion engines produce exhaust gases that contain a variety of pollutants, including hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides ("NOx"). Emission control systems that include exhaust catalytic conversion catalysts are widely used to reduce the amount of these pollutants emitted into the atmosphere. For compression ignition (i.e., diesel) engines, the most commonly used catalytic converter is the diesel oxidation catalyst (DOC). The DOC typically contains palladium and / or platinum, typically supported on alumina. This catalyst converts particulate matter (PM), hydrocarbons, and carbon monoxide into carbon dioxide and water.
[0003] In modern exhaust systems, DOCs are used during normal operation to control these CO and HC emissions. The role of the DOC in the passive oxidation of HC, CO, and NOx present in the exhaust gas stream occurs throughout the operation of the engine, and the operating window for the DOC is optimized between about 250°C and 300°C. The DOC can also be used to promote the conversion of NO to NO2 for downstream passive filter regeneration (particulate matter held on the filter is burned in NO2 at lower exhaust gas temperatures than O2 in the exhaust, the so-called effect).
[0004] Additionally, the DOC can be used as an exotherm generating catalyst. This is performed by injecting a hydrocarbon fuel into the exhaust gases. For the avoidance of doubt, fuel injection / exotherm generating events do not occur during normal operation: normal operation is considered to be the time interval between fuel injection / exotherm generating events. This second role of exotherm generation can be used for one of several purposes. For example, when an unacceptable increase in backpressure is detected, an exotherm can be generated to burn soot on a downstream filter. Another example is regeneration of an SCR catalyst, such as by removing sulfur from a downstream CuCHA SCR catalyst.
[0005] To generate these exotherms, a certain amount of hydrocarbons (HC) (2000 ppm) is injected upstream of the DOC. If the DOC is hot enough, the added HC will lead to the generation of an exotherm, heating the exhaust gas and therefore those downstream components (up to a temperature of about 500° C.). If the DOC is not hot enough, it will be necessary to provide hotter exhaust gas from the engine through engine management, with the associated energy and performance impacts.
[0006] Therefore, it is desirable to provide a DOC with a low exotherm generation temperature. The lower this temperature, the higher the probability that the engine is already operating above the exotherm temperature when exotherm is required, and / or the smaller the amount of energy that needs to be added to reach the proper operating temperature.
[0007] It is known that the performance characteristics of catalyst articles may change during the life of the catalyst article. Some of this performance can be regained with regeneration methods, but some performance is simply lost, such as by sintering platinum group metal (PGM) components. This can present difficulties when trying to provide a well-calibrated exhaust system that can operate optimally over the length of its useful life. In some cases, performance differences can provide such difficulties that it is actually desirable to pre-age the component prior to use to reach a point in its lifetime performance at which the performance differences observed by the end user are minimal. That is, the exhaust system manufacturer may prefer to sacrifice some fresh activity to ensure more consistent performance over the life of the component.
[0008] US8679434B1 discloses a method for preparing thermally stable powders. In particular, the present disclosure provides a honeycomb substrate on which a washcoat is disposed, the washcoat containing one or more calcined platinum group metal components dispersed on a refractory metal oxide support located on the honeycomb substrate, the platinum group metal component having an average crystallite size in the range of about 10 nm to about 25 nm to provide a stable NO2 to NOx ratio when exhaust gas flows through the honeycomb substrate. These powders, which have been aged to reduce their activity and thereby minimize performance changes during aging in use, can then be coated with the washcoat on the substrate to form a catalyst product. In use, the performance of the catalyst product is then more stable.
[0009] US20160236178A1 discloses the preparation of chemically reduced PGM materials that can be heat treated to give a preferred PGM size for NO oxidation. In particular, the present disclosure provides a method for preparing a catalyst composition for producing a stable NO2 to NO ratio in the exhaust system of a compression ignition engine. The method comprises: (i) preparing a first composition comprising a platinum (Pt) compound deposited or supported on a carrier material; (ii) preparing a second composition by reducing the platinum (Pt) compound to platinum (Pt) with a reducing agent; and (iii) heating the second composition to at least 650°C.
[0010] It is an object of the present invention to provide an improved method for manufacturing a DOC that solves the problems associated with the prior art and / or at least provides a commercially viable alternative.
[0011] According to a first aspect, the present invention provides a method for producing a diesel oxidation catalyst, the method comprising:
[0012] (i) providing a carrier substrate;
[0013] (ii) forming one or more platinum group metal-containing washcoat layers each comprising a refractory metal oxide support material on the support substrate to provide a first coated substrate;
[0014] (iii) subjecting the first coated substrate to a first thermal treatment to form a thermally treated coated substrate, wherein the first thermal treatment comprises heating the first coated substrate to a first maximum temperature and maintaining the first coated substrate at the first maximum temperature;
[0015] (iv) depositing a platinum group metal-containing composition comprising a refractory metal oxide support material on at least a portion of the heat-treated coated substrate to form a second coated substrate; and
[0016] (v) subjecting the second coated substrate to a second thermal treatment to form the diesel oxidation catalyst, wherein the second thermal treatment comprises heating the second coated substrate to a second maximum temperature and maintaining the second coated substrate at the second maximum temperature;
[0017] Wherein the first maximum temperature is at least 600°C, and wherein the second maximum temperature is at least 25°C lower than the first maximum temperature.
[0018] The present disclosure will now be further described. In the following paragraphs, different aspects / embodiments of the present disclosure are defined in more detail. Unless there is a clear contrary description, each aspect / embodiment so defined may be combined with any other aspect / embodiment or multiple aspects / embodiments. In particular, any feature indicated as being preferred or advantageous may be combined with any other one or more features indicated as being preferred or advantageous.
[0019] In the case of DOC, it is known from aging tests that heat treatment of the finished catalyst can be used to moderate the fresh catalytic activity. This has the effect of reducing the difference between fresh performance and aged performance. This is particularly advantageous for systems, such as those containing SCRF components, where low temperature activity may be sensitive to the NO / NO2 ratio. However, heat treating the finished catalyst will also moderate CO and HC handling and the exothermic activity of the catalyst, which is undesirable.
[0020] The inventors have now discovered that by performing a heat treatment at an intermediate stage, it is possible to selectively stabilize the NO oxidation activity and then apply another coating which provides the vast majority of fresh CO / HC and exothermic properties. This additional coating is ideally applied to the inlet as this is the part where CO / HC and exothermic properties are most needed. NO oxidation generally occurs at least in the rear of the catalyst, so this part should be applied before the stabilizing heat treatment is performed. Heat treatment at temperatures above 600°C is required to stabilize NO activity.
[0021] More specifically, the present invention relates to a method for making a diesel oxidation catalyst (DOC). The catalyst is typically in the form of a DOC article. A catalyst article refers to a single component used in an exhaust gas treatment system. These are sometimes also referred to as "bricks".
[0022] The method comprises providing a support substrate. This is the surface onto which the catalyst layer is subsequently applied and supported.
[0023] Preferably, the substrate is a flow-through monolith. The flow-through monolith substrate has a first face and a second face defining a longitudinal direction therebetween. The flow-through monolith substrate has a plurality of channels extending between the first face and the second face. The plurality of channels extend in the longitudinal direction and provide a plurality of inner surfaces (e.g., surfaces defining the walls of each channel). Each of the plurality of channels has an opening at the first face and an opening at the second face. The first face is typically at the inlet end of the substrate and the second face is at the outlet end of the substrate. For the avoidance of doubt, the flow-through monolith substrate is not a wall flow filter.
[0024] The channel may have a constant width, and each of the plurality of channels may have a uniform channel width. Preferably, the monolithic substrate has 300 to 900 channels / square inch, preferably 400 to 800 channels / square inch, in a plane orthogonal to the longitudinal direction. The channel may have a cross section of: rectangular, square, circular, elliptical, triangular, hexagonal or other polygonal shapes.
[0025] The monolith substrate acts as a support for holding the catalytic material. Suitable materials for forming the monolith substrate include ceramic-like materials such as cordierite, silicon carbide, silicon nitride, zirconium oxide, mullite, spodumene, alumina-silica magnesia or zirconium silicate or porous refractory metals. Such materials and their use in making porous monolith substrates are well known in the art.
[0026] It should be noted that the substrate described herein is a single component (i.e., a single brick), however, when forming an emission treatment system, the substrate used can be formed by adhering multiple channels together or by adhering multiple smaller substrates together, as described herein. Such techniques and suitable housings and configurations for emission treatment systems are well known in the art.
[0027] In embodiments where the catalyst article of the present invention comprises a ceramic substrate, the ceramic substrate may be made of any suitable refractory material, such as alumina, silica, ceria, zirconium oxide, magnesium oxide, zeolites, silicon nitride, silicon carbide, zirconium silicate, magnesium silicate, aluminosilicates, and metal aluminosilicates (such as cordierite and spodumene), or mixtures or mixed oxides of any two or more thereof. Cordierite, magnesium aluminosilicate, and silicon carbide are particularly preferred.
[0028] In embodiments where the catalyst article of the present invention comprises a metal substrate, the metal substrate may be made of any suitable metal, and in particular, of heat-resistant metals and metal alloys, such as titanium and stainless steel, and ferritic alloys containing iron, nickel, chromium and / or aluminum in addition to other trace metals.
[0029] The method comprises forming one or more washcoat layers containing a platinum group metal on a carrier substrate to provide a first coated substrate. The platinum group metals or PGMs as discussed herein are selected from a list comprising or consisting of ruthenium, rhodium, palladium, osmium, iridium and platinum. However, in practice, these preferably comprise or consist of platinum and palladium.
[0030] Preferably, the one or more washcoat layers containing a platinum group metal on the carrier substrate further comprise an alkaline earth metal, preferably strontium and / or barium.These materials are particularly useful for enhancing the exothermic heat generating properties of the DOC.
[0031] The formation of a carrier coating layer comprising PGMs is well known in the art. This generally involves preparing a carrier coating slurry. This involves mixing a variety of ingredients together. The term "slurry" as used herein may encompass a liquid comprising an insoluble material (e.g., insoluble particles). The slurry may comprise (1) a solvent; (2) a soluble content, such as free PGM ions (i.e., outside the carrier); and (3) an insoluble content, such as carrier particles. Slurries are particularly effective in placing the material on a substrate, particularly for maximizing gas diffusion and minimizing pressure drop during catalytic conversion. The slurry is typically stirred, more typically for at least 10 minutes, more typically for at least 30 minutes, and even more typically for at least one hour. For example, stirring of the slurry may be performed prior to placing the slurry on the substrate.
[0032] The first preferred component in the carrier coating slurry is a carrier material. The carrier material is typically a refractory metal oxide powder. Preferably, the refractory metal oxide carrier material is selected from alumina, silica, zirconia, ceria and composite oxides or mixed oxides of two or more thereof, most preferably selected from alumina, silica and zirconia and composite oxides or mixed oxides of two or more thereof. Mixed oxides or composite oxides include silica-alumina and ceria-zirconia, most preferably silica-alumina. Preferably, the refractory metal oxide carrier material does not contain ceria or mixed oxides or composite oxides containing ceria. More preferably, the refractory oxide is selected from alumina, silica and silica-alumina. The refractory oxide may be alumina. The refractory oxide may be silica. The refractory oxide may be silica-alumina.
[0033] The inclusion of a dopant can stabilize the refractory metal oxide support material or promote the catalytic reaction of the supported platinum group metal. Typically, the dopant can be selected from the group consisting of zirconium (Zr), titanium (Ti), silicon (Si), yttrium (Y), lanthanum (La), praseodymium (Pr), samarium (Sm), neodymium (Nd), barium (Ba), and their oxides. Generally speaking, the dopant is different from the refractory metal oxide (i.e., the cation of the refractory metal oxide). Thus, for example, when the refractory metal oxide is titanium dioxide, the dopant is not titanium or its oxide.
[0034] When the refractory metal oxide support material is doped with a dopant, then typically the refractory metal oxide support material comprises a total amount of 0.1 wt% to 10 wt% of the dopant. The total amount of dopant is preferably 0.25 wt% to 7 wt%, more preferably 2.5 wt% to 6.0 wt%. Preferably, the dopant is silica, because oxidation catalysts comprising such support materials in combination with platinum group metals and alkaline earth metals promote oxidation reactions, such as CO and hydrocarbon oxidation.
[0035] Preferably, the support material is selected from the group consisting of optionally doped alumina, silica, titania and combinations thereof.
[0036] Another ingredient in the washcoat is a PGM component, preferably a salt of a PGM component. Thus, the washcoat typically contains a palladium (Pd) salt and / or a platinum (Pt) salt. Preferably, these salts are readily soluble in water. Preferably, the Pd and Pt salts are independently selected from nitrates, chlorides and bromides. Preferably, the washcoat slurry is free of Rh. Preferably, the platinum group metal present in the washcoat slurry consists of Pt and Pd.
[0037] There may also be other optional ingredients commonly used to form the carrier coating slurry. These include one or more of a binder and a thickener. The binder may include, for example, an oxide material having a small particle size to bind the individual insoluble particles in the carrier coating slurry together. The use of binders in carrier coatings is well known in the art. The thickener may include, for example, a natural polymer having functional hydroxyl groups that interact with the insoluble particles in the carrier coating slurry. It is used for the purpose of thickening the carrier coating slurry to improve the coating profile during the application of the carrier coating coating to the substrate. It is usually burned off during the calcination of the carrier coating. Examples of specific thickeners / rheology modifiers for carrier coatings include soy gum, guar gum, xanthan gum, curdlan, schizophyllan, scleroglucan, diutan gum, welan gum, hydroxymethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, methyl hydroxyethyl cellulose, methyl hydroxypropyl cellulose and ethyl hydroxy cellulose.
[0038] The solids content of the slurry is preferably 10% to 40%, preferably 15% to 35%. Such solids content can make the slurry rheology suitable for placing the loaded support material on the substrate. For example, if the substrate is a honeycomb monolith, such solid content can make a thin layer of washcoat deposited on the inner wall of the substrate.
[0039] Forming a carrier coating layer to obtain a coated substrate involves applying a carrier coating slurry to at least a portion of the substrate to form a carrier coating coated substrate. The slurry can be disposed on the substrate using techniques known in the art. Typically, a specific molding tool can be used to pour the slurry into the inlet of the substrate in a predetermined amount, thereby disposing the loaded carrier material on the substrate. As discussed in more detail below, subsequent vacuum and / or air knife and / or drying steps can be used during this disposition step. When the carrier is a filter block, the loaded carrier material can be disposed on the filter wall, in the filter wall (if porous), or both.
[0040] Prior to coating, the pH of the slurry may be adjusted using nitric acid or citric acid and optionally a base such as ammonia or barium hydroxide to obtain the desired pH. The use of a base may be used to ensure that the pH is not adjusted to too low a pH.
[0041] The method then comprises subjecting the first coated substrate to a first heat treatment to form a heat treated coated substrate. The first heat treatment comprises heating the first coated substrate to a first maximum temperature and maintaining the first coated substrate at the first maximum temperature. As will be appreciated, a typical heat treatment process involves passing the substrate through a furnace with a temperature rise zone. The maximum temperature reached has a major effect on the heated substrate. Therefore, the key parameters of the heat treatment process are the temperature reached and the time spent at this temperature.
[0042] The first maximum temperature is at least 600°C. Preferably, the first maximum temperature is 625 to 750°C, preferably 650 to 700°C. Preferably, the first coated substrate is maintained at the first maximum temperature for at least 30 minutes, preferably 1 hour to 3 hours. Shorter times may not be sufficient to achieve the desired aging, while longer times are less desirable commercially. Excessively long times may result in an undesirably high level of aging and a complete loss of the desired properties. The first heat treatment may be carried out under aqueous conditions, although ambient moisture is sufficient, but preferably aging is carried out under conditions of 5 wt % to 15 wt % H2O.
[0043] The first heat treatment can be carried out in two steps. The first step is a conventional calcination step, which can then be followed by a second aging step. However, preferably, the aging step is sufficient to carry out calcination and aging simultaneously.
[0044] Although the calcination step can be carried out within a certain temperature range when forming the catalyst product, the optimal temperature is determined by the properties of the carrier coating and the application of the final catalyst. In general, it is desirable to use the lowest temperature that still causes suitable calcination, because this results in the lowest process cost and has the lowest possibility of damaging the product. Typically, the DOC calcination temperature is in the range of about 500°C (such as 450°C-550°C), because this is sufficient to calcine the component without excessive damage or loss of function. Therefore, the first heat treatment of the present invention is carried out at a temperature higher than the normal calcination step. In addition, the purpose of the first heat treatment is to achieve aging of the component so that the combination of the highest temperature reached and the time spent at this temperature is greater than the normal calcination step.
[0045] The one or more washcoat layers containing a platinum group metal formed on the substrate preferably provide a 10 g / ft2 surface area of the coated substrate after the first heat treatment. 3 Up to 50g / ft 3 , more preferably 20g / ft 3 Up to 40g / ft 3 PGM loading.
[0046] The one or more washcoat layers containing a platinum group metal preferably together cover substantially the entire length of the substrate. That is, preferably the coated substrate has a continuous platinum group metal-containing coating extending from the inlet end to the outlet end of the support substrate. Alternatively, the one or more washcoat layers containing a platinum group metal may together cover at least 40%, more preferably at least 60%, and most preferably at least 80% of the axial length of the substrate. Such coverage preferably extends from the outlet end.
[0047] When the coated substrate has a continuous platinum group metal-containing coating extending from the inlet end to the outlet end of the carrier substrate, it is preferred to divide the continuous platinum group metal-containing coating into zones, wherein the inlet zone comprises Pt and Pd, and the outlet zone comprises Pt and optionally Pd. Preferably, the continuous platinum group metal-containing coating consists of an inlet zone and an outlet zone.
[0048] After the first heat treatment, the method further includes depositing a platinum group metal-containing composition on at least a portion of the heat-treated coated substrate to form a second coated substrate. That is, a fresh layer or zone of the platinum group metal-containing composition is formed on the aged coated substrate. This provides fresh PGM material for CO and HC oxidation, as well as potential exothermic heat generation properties.
[0049] The fresh layer or zone may be applied by a range of techniques, including application of a washcoat, as described above. Alternatively, the fresh layer or zone may be obtained by direct impregnation of the aged coated substrate (or a portion thereof) with a salt of the PGM.
[0050] Preferably, the fresh layer or zone is provided only on the upstream portion of the substrate extending from the inlet end of the substrate. Preferably, the washcoat is provided over less than 40% of the axial length of the substrate, preferably over 10% to 30% of the axial length, extending from the inlet end of the substrate. Typically, the fresh layer or zone will be located entirely over the initial one or more platinum group metal-containing washcoat layers. However, in embodiments where the one or more platinum group metal-containing washcoat layers do not extend the full length, there may be no or only partial overlap between the fresh layer or zone and the aged coating on the substrate.
[0051] After depositing the platinum group metal-containing composition on at least a portion of the heat-treated coated substrate to form a second coated substrate, the second coated substrate is subjected to a second heat treatment to form a diesel oxidation catalyst, wherein the second heat treatment comprises heating the second coated substrate to a second maximum temperature and maintaining the second coated substrate at the second maximum temperature. It is required that the second maximum temperature is at least 25°C lower than the first maximum temperature. Preferably, the second maximum temperature is at least 50°C lower than the first maximum temperature, more preferably 100°C to 250°C lower.
[0052] Ideally, the second heat treatment step is a conventional calcination step. Preferably, the second heat treatment is carried out at a second maximum temperature of 400° C. to 575° C., preferably 450° C. to 550° C. Preferably, the second heat treatment is carried out while maintaining the second coated substrate at the second maximum temperature for at least 30 minutes, preferably 1 hour to 3 hours.
[0053] As will be appreciated, in a conventional process with multiple layers with intermediate calcination steps applied, each calcination step will be carried out under the same conditions. There is no reason to switch heat treatment temperatures, and certainly no reason to make the temperature of the first heat treatment higher than the temperature of the second heat treatment.
[0054] The first heat treatment and the second heat treatment are usually carried out in an oven or furnace, more usually in a belt or static oven or furnace, usually in hot air with a specific flow from one direction. Any step may also include an initial drying step. The drying step and the heat treatment step may be continuous or sequential. For example, a separate carrier coating can be applied after the substrate has been coated with a carrier coating and dried with a previous carrier coating. If the coating is completed, a continuous heating program can also be used to dry and heat treat the substrate coated with the carrier coating. During heating, any complex that may be formed in the solution may be at least partially, substantially or completely decomposed. In other words, the ligand of this complex (such as an organic compound) can be at least partially, substantially or completely removed or separated from the PGM ion, and can be removed from the final catalyst product. Then the particles of this separated palladium can begin to form metal-metal bonds and metal-oxide bonds. As a result of heating (calcining), the substrate is usually substantially free of the organic compound, more usually completely free of the organic compound.
[0055] After each heating step, the substrate is typically cooled, more typically to room temperature. Cooling is typically performed in air with or without a coolant / medium, typically without a coolant.
[0056] It has been found that efficient exotherm generation is best achieved with high PGM loading in the front region of the DOC. This means that exotherm is generated in the front of the DOC, but the back of the DOC experiences a strong heating effect. By having a higher PGM concentration in the cooler front, the article has improved life and durability because this portion does not experience the highest temperatures.
[0057] According to a preferred configuration, the DOC has a front zone extending from the inlet end, which has a higher PGM concentration than the rear zone extending from the inlet end. Preferably, the PGM concentration is at least 2 times greater in the front zone, more preferably at least 4 times greater and preferably 4 to 10 times greater. Due to the lower PGM content, the rear portion, which generally has a lower PGM content, is more resistant to sintering. That is, when the rear zone has a lower PGM loading, they are spaced farther apart and are less likely to sinter together. Using a smaller amount of PGM in the rear zone is more efficient for PGM use. Using a higher amount in the front zone allows for efficient exothermic generation, but does not compromise performance. The front zone will perform passive CO and HC oxidation, while the rear zone is sufficient to handle the competitive NOx oxidation that also needs to occur.
[0058] Preferably, the outlet zone (rear zone) has a smaller Pt loading than the inlet zone (front zone), expressed in g / in 3 This is useful for efficient exothermic generation embodiments. In another embodiment, the outlet zone has a greater Pt loading than the inlet zone, measured in g / in 3 count.
[0059] According to a preferred embodiment, there is provided a method for manufacturing a diesel oxidation catalyst, the method comprising:
[0060] (i) providing a carrier substrate;
[0061] (ii) forming one or more washcoat layers containing a platinum group metal on a carrier substrate to provide a first coated substrate, wherein the one or more washcoat layers containing a platinum group metal are over 100% of the axial length of the carrier and comprise Pt and optionally Pd;
[0062] (iii) subjecting the first coated substrate to a first thermal treatment to form a thermally treated coated substrate, wherein the first thermal treatment comprises heating the first coated substrate to a first maximum temperature and maintaining the first coated substrate at the first maximum temperature;
[0063] (iv) depositing a platinum group metal-containing composition on at least a portion of the heat-treated coated substrate to form a second coated substrate, the composition forming an inlet zone over 10% to 40% of the axial length of the carrier substrate; and
[0064] (v) subjecting the second coated substrate to a second thermal treatment to form the diesel oxidation catalyst, wherein the second thermal treatment comprises heating the second coated substrate to a second maximum temperature and maintaining the second coated substrate at the second maximum temperature;
[0065] The first maximum temperature is 600°C to 750°C, and the first heat treatment is performed for 1 hour to 3 hours in a water-containing atmosphere containing 5 wt% to 15 wt% H2O, and the second maximum temperature is 450°C to 550°C in air.
[0066] According to a preferred embodiment, there is provided a method for manufacturing a diesel oxidation catalyst, the method comprising:
[0067] (i) providing a carrier substrate;
[0068] (ii) forming one or more washcoat layers containing a platinum group metal on a carrier substrate to provide a first coated substrate, wherein the one or more washcoat layers containing a platinum group metal are over 100% of the axial length of the carrier and comprise Pt and optionally Pd;
[0069] (iii) subjecting the first coated substrate to a first thermal treatment to form a thermally treated coated substrate, wherein the first thermal treatment comprises heating the first coated substrate to a first maximum temperature and maintaining the first coated substrate at the first maximum temperature;
[0070] (iv) depositing a platinum group metal-containing composition on at least a portion of the heat-treated coated substrate to form a second coated substrate, the composition forming an inlet zone over 10% to 40% of the axial length of the carrier substrate; and
[0071] (v) subjecting the second coated substrate to a second thermal treatment to form the diesel oxidation catalyst, wherein the second thermal treatment comprises heating the second coated substrate to a second maximum temperature and maintaining the second coated substrate at the second maximum temperature;
[0072] Wherein the first maximum temperature is a temperature of 650°C to 725°C, and the first heat treatment is carried out in a water-containing atmosphere containing 5 wt% to 15 wt% H2O for 1 hour to 3 hours, and wherein the second maximum temperature is 475°C to 525°C in air for 1 hour to 3 hours.
[0073] It should be understood that the above method defines an intermediate aging treatment (first heat treatment) and a final calcination step (second heat treatment) in order to describe the production of a DOC having an aged platinum group metal-containing carrier coating layer thereon and a fresh platinum group metal-containing composition deposited on its inlet end. An alternative way to consider this is to consider the dispersion of the PGM material in each layer. When PGMs are applied to the carrier coating, they are typically finely dispersed, and aging results in a sintering effect that forms larger PGM agglomerates. This means that the degree of aging can be determined by examining the PGM dispersion. The product of the method described herein provides a unique structure having larger agglomerates of aging in the underlying carrier coating layer, but having fresh, finely dispersed PGMs in the upper layer (or impregnated in the underlying carrier coating layer, giving a multimodal distribution).
[0074] Whether the PGM-containing layer has been aged can be determined using known techniques. Inductively coupled plasma optical emission spectroscopy (ICP-OES) can be used to evaluate the form and condition of the PGM component in the catalyst. In this way, the extent of aging can be determined, thereby demonstrating how part of the catalyst is aged while part is still fresh. For the measurements, a Micromeritics Autochem 2920 instrument was used to measure the CO uptake of the sample. The sample was pretreated with hydrogen at 300°C. Carbon monoxide uptake was measured by pulse chemisorption at 50°C. The Autochem 2920 software can then be used to calculate the PGM material dispersion and particle size based on the CO uptake and PGM material content of the sample. The dispersion of the PGM material is a measure of the particle size of the PGM material. Large particles with low surface area have low dispersion. Therefore, this technique allows the determination of the extent to which the applied PGM is sintered together by aging.
[0075] Preferably, the aged platinum group metal-containing washcoat layer comprises platinum group metal particles having an average particle size (D50) greater than 10 nm as determined by TEM, and the fresh platinum group metal-containing composition comprises platinum group metal particles having a D90 particle size less than 10 nm as determined by TEM. It is possible to assess these characteristics by TEM examination of each layer or zone applied.
[0076] According to another aspect, there is provided a diesel oxidation catalyst article comprising a flow-through carrier substrate having an aged washcoat layer containing a platinum group metal thereon, and a fresh platinum group metal-containing composition deposited on an inlet end thereof, wherein the aged washcoat layer containing a platinum group metal comprises platinum group metal particles having an average particle size (D50) greater than 10 nm as determined by TEM, and the fresh platinum group metal-containing composition comprises platinum group metal particles having a D90 particle size less than 10 nm as determined by TEM. Advantageously, this configuration provides stable NO oxidation without significant impact on CO / HC and exothermic activity.
[0077] Preferably, a diesel oxidation catalyst is obtained or obtainable by the process described herein.
[0078] According to another aspect, there is provided an exhaust treatment system comprising a diesel oxidation catalyst as described herein, the diesel oxidation catalyst being arranged upstream of one of:
[0079] (A) Soot filter;
[0080] (B) SCR catalyst products;
[0081] (C) SCRF catalyst products;
[0082] (D) catalyzed soot filters;
[0083] (E) a soot filter followed by an SCR catalyst article; or
[0084] (F) Catalyzed soot filter followed by SCR catalyst article.
[0085] These components are well known in the art. These components can benefit from providing a DOC obtained by the method disclosed herein in one of two ways at an upstream position. Some of these components (such as the soot filter) benefit from the exothermic supply capability of the DOC. This additional heat is used to enhance soot combustion and removal. Other components of these components particularly benefit from stable NO2 production capabilities.
[0086] This is especially true for SCR and SCRF components. Selective catalytic reduction (SCR) of NOx occurs primarily through the following three reactions:
[0087] (1)4 NH3+4 NO+O2→4 N2+6 H2O;
[0088] (2) 4NH3+2NO+2NO2→4N2+6H2O; and
[0089] (3)8 NH3+6 NO→7 N2+12 H2O.
[0090] The ratio of NO2:NO in the exhaust gas entering the SCR catalyst or SCRF catalyst can therefore affect its performance (see reaction 2). Generally, SCR catalysts or SCRF catalysts exhibit optimal performance when the ratio of NO2:NO is about 1:1. This can be problematic because the exhaust gas generated by a compression ignition engine during normal use generally contains insufficient NO2 (i.e., the ratio of NO2:NO is much less than 1:1) for optimal performance of the SCR catalyst or SCRF catalyst.
[0091] To compensate for this low level of NO2, DOCs are formulated to oxidize nitric oxide (NO) to nitrogen dioxide (NO2), thereby increasing the ratio of NO2:NO in the exhaust.By providing an improved DOC in which NO2 production levels are maintained throughout the operating life, the level of PGMs in the component can be optimized.
[0092] According to another aspect, a diesel combustion and exhaust treatment system is provided that includes a diesel combustion engine and the exhaust system described herein.
[0093] According to another aspect, there is provided a method for making the exhaust system described herein, the method comprising forming a diesel oxidation catalyst according to the method described herein and arranging it upstream of any one of (A) to (F).
[0094] definition
[0095] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0096] The use of the term "comprising" is intended to be interpreted as including such features but not excluding other features, and is also intended to include feature options that must be limited to those described. In other words, the term also includes the limitations "essentially consisting of" (intended to indicate that certain additional components may be present, provided that they do not materially affect the basic characteristics of the described features) and "consisting of" (intended to indicate that other features may be excluded, such that if these components are expressed in percentages of their proportions, these will add up to 100%, taking into account any unavoidable impurities), unless the context clearly indicates otherwise.
[0097] As used herein, the term "on" is intended to mean "directly on," such that there are no intervening layers between one material that is referred to as being "on" another material. Spatially relative terms, such as "below," "beneath," "lower," "above," "upper," and the like, may be used herein to facilitate describing the relationship of one element or feature to another. It should be understood that the spatially relative terms are intended to encompass different orientations of the catalyst in use or operation in addition to the orientation depicted in the accompanying drawings.
[0098] The term "calcine" or "calcination" means heating a material in air or oxygen. This definition conforms to the IUPAC definition of calcination (IUPAC. Compendium of Chemical Terminology, 2nd Edition ("Golden Book"), compiled by AD McNaught and A. Wilkinson, Blackwell Scientific Publications, Oxford (1997). XML online corrected version: http: / / goldbook.iupac.org (2006-), created by M. Nic, J. Jirat, B. Kosata; updated by A. Jenkins, ISBN 0-9678550-9-8.doi: 10.1351 / goldbook). The temperature used in the calcination depends on the components in the material to be calcined. According to Chapter 2.3.3 and Chapter 2.3.4 of RM Heck et al., "Catalytic Air Pollution Control - Commercial Technology", John Wiley & Sons, Inc., 3rd Edition (2009), the washcoat-coated catalytic species (including platinum and palladium salts) on the monolithic substrate for automotive applications are forced air dried at about 110° C. and calcined in forced air to about 400° C.-500° C. to remove all traces of decomposable salts used to prepare the catalyst. In applications involving the process described herein (i.e., conventional DOC preparation and secondary heat treatment), calcination is typically carried out at a temperature of about 400° C. to about 600° C. for about 1 hour to 8 hours, preferably at a temperature of about 400° C. to about 550° C. for about 1 hour to 4 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0099] The invention will now be further described with reference to the following non-limiting drawings, in which:
[0100] Figure 1 A schematic diagram of the layers formed in the methods described herein is shown.
[0101] Figure 2 A flow chart showing the key steps of the method described herein.
[0102] Figure 3 The NO2 / NOx performance of a conventional DOC and a DOC prepared according to the present invention at different temperatures is shown.
[0103] Figure 4 shows the PGM particle size of conventional DOC, and Figure 5 The PGM particle size of DOC prepared according to the present invention is shown.
[0104] like Figure 1 As shown in FIG. 1 , a DOC 1 is provided. The DOC 1 comprises a substrate 5. The substrate 5 is preferably a flow-through substrate, such as in the form of porous cordierite. The substrate 5 has an inlet end 10 for receiving the exhaust gas to be treated and an outlet end 15 for releasing the treated exhaust gas. The exhaust gas flow direction is shown by arrow 20.
[0105] The substrate 5 has a PGM-containing layer 25 provided along the entire length of the substrate 5 by application of a washcoat. This is typically a layer containing only Pt or containing Pd and Pt. The total PGM content of this layer is typically 10 g / ft 3 Up to 50g / ft 3 The PGM content is provided on a support material, such as alumina. The PGM-containing layer 25 has been subjected to an ageing process, which stabilizes the NO oxidation properties of the layer.
[0106] On top of the PGM-containing layer 25, a further PGM-containing zone 30 is provided at the inlet end 10. This may be applied by washcoat or impregnation etc. This zone 30 preferably comprises Pt and typically provides a further 10 g / ft 3 Up to 50g / ft 3 This zone 30 has not been subjected to an aging process, so it has a fresh activity. This provides enhanced exothermic generation at the inlet of the DOC.
[0107] like Figure 2 As shown in , the method includes:
[0108] (A) providing a carrier substrate 5;
[0109] (B) forming a PGM-containing layer 25 on a carrier substrate 5;
[0110] (C) aging the PGM-containing layer 25 on the carrier substrate 5 at a temperature of 650° C. for a period of 1 hour to 3 hours in an atmosphere containing 10 wt % moisture;
[0111] (D) A PGM-containing region 30 is formed on the aged PGM-containing layer 25 on the carrier substrate 5 .
[0112] like Figure 3 As shown in , the conventional reference DOC exhibits a large drop in NO2 / NOx performance between the fresh (i.e., degreened) performance and the aged performance (650°C, 140 hours). In contrast, the DOC prepared according to the present invention exhibits a much smaller difference between the fresh (i.e., degreened) performance and the aged performance (650°C, 140 hours). The DOC prepared according to the present invention was first heat treated at 700°C for 3 hours.
[0113] Figure 4The PGM particle size in the reference fraction showed a significant variation between a starting size of about 6 nm (D90 less than 10 nm) and a broad distribution after aging (D50 greater than 10 nm). Figure 5 It shows how the PGM particle size of the DOC obtained according to the present invention has a starting size with a D50 above 10 nm. After aging, the particle size is generally lower than in the comparative data. That is, the variation of the PGM particle size in the DOC of the present invention is lower.
[0114] It should be noted that Figure 4 and Figure 5 Only the PGM particle size in the one or more washcoat layers containing a platinum group metal on the carrier substrate is taken into account. Thus, the DOC obtained according to the present invention will have an additional distribution of PGMs (such as in the washcoat layer) having a D90 of less than 15 nm, preferably less than 10 nm. Example
[0115] The invention will now be further described with reference to the following non-limiting examples.
[0116] The invention will now be illustrated by the following non-limiting examples. For the avoidance of doubt, all coating steps were carried out using the method and apparatus disclosed in the applicant's WO99 / 47260, i.e. the method comprising the steps of: (a) positioning a containment device on top of a substrate, (b) dosing a predetermined amount of a liquid component into said containment device in the order of (a) then (b) or (b) then (a), and (c) by applying a vacuum, sucking the entire amount of the liquid component into at least a portion of the substrate and retaining substantially the entire amount within the substrate without recirculation.
[0117] Example 1 (reference)
[0118] A bare cordierite honeycomb flow-through substrate monolith 13 inches long by 5 inches in diameter was coated with a catalyst washcoat in the following zoned arrangement. A first catalyst washcoat slurry containing aqueous salts of platinum and palladium (as nitrates) and a particulate gamma-alumina support material was applied to the substrate monolith from one end marked as the inlet end to an axial length of 80% of the total substrate monolith length. The concentrations of the platinum and palladium salts were selected to achieve a weight ratio of platinum to palladium of 6.65 Pt:6.65 Pd gft in the coating at a 1:1 platinum to palladium ratio in the first catalyst washcoat coating. -3 The load capacity is 13.3gft -3 The inlet coating was then dried in a conventional oven at 100°C for 1 hour to remove excess water and other volatile materials.
[0119] A second catalyst washcoat slurry comprising an aqueous solution of a platinum nitrate salt as the only platinum group metal present and a particulate gamma-alumina support material was applied to the substrate coated with the first coating from the end of the substrate monolith opposite to the end to which the first coating was applied (i.e., the outlet end). The axial length of the second catalyst washcoat coating was 75% of the total substrate length, i.e., 50% of the second washcoat catalyst coating overlapped with the first washcoat catalyst coating. The concentration of platinum salt used was selected to achieve 2.02 gft in the 75% axial substrate length coated. -3 Pt loading. The substrate coated with both the first and second washcoat coatings was dried in a conventional oven at 100°C for 1 hour and the dried portion was then calcined at 500°C for 1 hour to decompose the platinum and palladium salts and fix the platinum and palladium to the particulate gamma-alumina support material.
[0120] An aqueous medium containing salts of both platinum nitrate and palladium nitrate in a 1:1 weight ratio was then impregnated onto the coating of the first catalyst support wash to 25% of the substrate axial length measured from the substrate inlet end. The salt concentration was selected to achieve 35 gft each of platinum and palladium in the substrate over the impregnated length. -3 This provides a high PGM loading in the zone at the inlet end, with an additional loading of 35 gft over and above that of the underlying first catalyst washcoat coating. -3 The impregnated part was dried in a conventional oven at 100°C for 1 hour and the dried part was then calcined at 500°C for 1 hour.
[0121] All washcoat and impregnation solutions were naturally acidic and no pH adjustment was performed on them.
[0122] The finished product comprises a substrate monolith comprising three catalyst washcoat zones arranged axially in series: a first high loading front zone defined as approximately 25% of the axial length of the substrate monolith measured from the inlet end and having a total platinum group metal loading that is a combination of the following 1Pt:1Pd first catalyst washcoat and impregnated 1:1Pt:Pd; followed by an axially connected second catalyst washcoat zone comprising a second Pt-only catalyst washcoat superimposed on approximately 50% of the axial length of the 1Pt:1Pd first catalyst washcoat at a lower total platinum group metal loading than the first catalyst washcoat zone; and a third Pt-only zone at the outlet end consisting of a coating of the second catalyst washcoat of approximately 25% of the axial length of the substrate monolith having a lower total platinum group metal loading than the first or second catalyst washcoat zones. The total platinum group metal loading on the substrate monolith as a whole is 21 gft -3, the total Pt:Pd weight ratio was 7:6, equivalent to 1.167: 1. The resulting catalyst is described herein as "fresh", ie as prepared.
[0123] Example 2 (Comparative)
[0124] The same product as disclosed in Reference Example 1 was prepared except that the impregnated portion was dried in a conventional oven at 100°C for 1 hour and then the dried portion was calcined at 700°C for 3 hours. The resulting catalyst is described herein as "fresh", ie as prepared.
[0125] Example 3
[0126] A product similar to Comparative Example 2 was prepared, except that the order of the calcination and impregnation steps was reversed. That is, after calcining the substrate coated with the first overlapping coating and the second overlapping coating at 500°C for 1 hour, the product was further aged by calcining to 700°C in air for 3 hours. The first catalyst support coating of the product was then impregnated with an aqueous medium containing salts of both platinum nitrate and palladium nitrate in a weight ratio of 1:1 to 25% of the axial length of the substrate measured from the inlet end of the substrate. The impregnated portion was oven dried at 100°C for 1 hour, and the dried portion was then calcined at 500°C for 1 hour. The resulting catalyst is described herein as "fresh", i.e., as prepared.
[0127] Example 4 - Test Methods
[0128] Thermal analysis was performed on each aged composite oxidation catalyst prepared according to Reference Example 1, Comparative Example 2 and Example 3 (according to the present invention) using a laboratory bench mounted diesel engine. The engine was operated at 2200 rpm with EUVI B7 fuel (7% biofuel) as the fuel for engine operation and exhaust hydrocarbon enrichment (exothermic generation) and was equipped with an exhaust system comprising an exhaust pipe and a removable canister into which each composite oxidation catalyst could be inserted for testing, with the inlet end / first catalyst, high load carrier coating layer zone oriented to the upstream side. The engine was a 7 liter capacity EUV 6 cylinder engine, producing 235 kW at 2500 rpm, and the exhaust system included a "7th injector" which was arranged to inject hydrocarbon fuel directly into the exhaust pipe, which was downstream of the engine manifold and upstream of the composite oxidation catalyst to be tested. This injector is referred to as the "7th injector" because it is in addition to the six fuel injectors associated with the engine cylinders. Thermocouples were located at the inlet of the composite oxidation catalyst and inserted at various axial positions along the centerline of the substrate monolith of each composite oxidation catalyst.
[0129] The degreened fresh (see below) and aged NO oxidation activity of each catalyst was performed as follows. Aging was performed as follows. Each composite oxidation catalyst prepared according to Reference Example 1, Comparative Example 2 and Example 3 (according to the present invention) was tested for average NO after oven aging at 650°C in air for 140 hours, corresponding to the activity at the end of vehicle life. Detected NO2 / Total NO x The speed / load diagram was obtained and the integrated average values of the mass flow rate from 400 kg / hour to 1000 kg / hour versus the catalyst inlet temperature from 200°C to 350°C in the quadrant were calculated and recorded in Table 1 below.
[0130] The exotherm test was conducted as follows. Each aged catalyst was conditioned at an inlet exhaust gas temperature of 490°C with an exhaust gas flow rate of 1000 kg / hr for 10 minutes followed by a rapid cooling step, a process known as "de-greening"). The exhaust gas flow rate was then set to 720 kg / hr (corresponding to 120,000 hr -1 space velocity of the size and volume of the substrate being tested), while controlling the engine load so that a steady-state set inlet exhaust temperature of about 270° C. is achieved at about 1800 seconds.
[0131] The ability of the composite oxidation catalyst to generate an exotherm at each stable set temperature was then tested by injecting hydrocarbon fuel via a seventh injector, which had a target temperature of 600°C, and generating a stable hydrocarbon "leak" at the outlet of the composite oxidation catalyst substrate via a downstream thermocouple and hydrocarbon sensor. If the hydrocarbon slip measured downstream of the composite oxidation catalyst exceeded 1000 ppm C3, that is, regardless of the hydrocarbon chain length in the detected hydrocarbons - the modal carbon chain length in a typical diesel fuel is C 16 - If the detection is equal to 1000ppm C3, the test will be stopped. Therefore, if 187.5ppmC is detected 16 , this is equivalent to 1000ppm C3(C 16 Equivalent to 5 1 / 3×C3 hydrocarbons).
[0132] After testing at a set inlet temperature of about 270°C, the system was preconditioned again at an inlet exhaust temperature of 490°C for 10 minutes at a flow rate of 1000 kg / hour, and then rapidly cooled and tested for heat release at a second set temperature (e.g., about 260°C). This cycle was repeated to test heat release generation at set temperatures of about 250°C, 240°C, and 230°C. The test was stopped when the composite oxidation catalyst failed to generate a stable heat release of 600°C at the end of the composite oxidation catalyst outlet or when the hydrocarbon slip measured at the composite oxidation catalyst outlet exceeded 1000 ppm (C3).
[0133] Table 1
[0134]
[0135] The results of these tests conducted on Reference Example 1, Comparative Example 2 and Example 3 (according to the present invention) are listed in Table 1 below. It should be understood that the lower the inlet temperature at which a stable exotherm can be achieved with acceptable hydrocarbon slip, the more advantageous it is. This is because the design flexibility in the system is increased because the filter regeneration event can be started from a lower inlet exhaust gas temperature, that is, there is no need to wait until the exhaust gas temperature under normal operating conditions is high enough to trigger filter regeneration, which may occur less frequently in ordinary operation. In addition, it improves overall fuel economy because it is not necessary to inject as many hydrocarbons in order to achieve the desired exhaust gas temperature at the outlet of the composite oxidation catalyst.
[0136] Additionally, from the oxidation activity of each catalyst, it can be seen that the difference in NO oxidation activity from fresh to aged is lower for Comparative Example 2 (37.8% minus 33.1% = 4.7%) and Example 3 (according to the invention) (41.0% minus 35.2% = 5.8%) than for Reference Example 1 (54.6% minus 43.7% = 10.9%). The lower the "difference" between fresh and aged catalyst activity, the easier it is for OEM customers to program the engine control unit with an algorithm that allows the NO oxidation catalyst activity to decrease over time and adjust the urea injection on the downstream SCR catalyst accordingly; or use an active regeneration event between events. effect, programming shortened intervals in downstream active filter regeneration using passive soot combustion in NO2.
[0137] Therefore, the catalyst of Example 3 according to the invention combines a lower average NO2 / NO2 ratio between fresh and aged than that of Reference Example 1. x ratio difference; and a lower ability to generate exotherm at lower temperatures than Comparative Example 2.
[0138] The foregoing detailed description has been provided by way of explanation and illustration and is not intended to limit the scope of the appended claims. Many variations of the presently preferred embodiments shown herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.
[0139] For the avoidance of doubt, any and all documents cited herein are hereby incorporated by reference into this application in their entirety.
Claims
1. A method for producing a diesel oxidation catalyst, the method comprising: (i) providing a carrier substrate; (ii) forming one or more platinum group metal-containing washcoat layers each comprising a refractory metal oxide support material on the support substrate to provide a first coated substrate; (iii) subjecting the first coated substrate to a first thermal treatment to form a thermally treated coated substrate, wherein the first thermal treatment comprises heating the first coated substrate to a first maximum temperature and maintaining the first coated substrate at the first maximum temperature; (iv) depositing a platinum group metal-containing composition comprising a refractory metal oxide support material on at least a portion of the heat-treated coated substrate to form a second coated substrate; and (v) subjecting the second coated substrate to a second thermal treatment to form the diesel oxidation catalyst, wherein the second thermal treatment comprises heating the second coated substrate to a second maximum temperature and maintaining the second coated substrate at the second maximum temperature; wherein the first maximum temperature is at least 600°C, and wherein the second maximum temperature is at least 25°C lower than the first maximum temperature.
2. The method according to claim 1, wherein the first heat treatment is performed in a moisture-containing atmosphere.
3. The method according to claim 1 or claim 2, wherein the first heat treatment is performed as follows: (a) the first maximum temperature is 625°C to 750°C, preferably 650°C to 700°C; and / or (b) maintaining the first coated substrate at the first maximum temperature for at least 30 minutes, preferably 1 hour to 3 hours; and / or (c) at 5 wt % to 15 wt % H2O.
4. The method according to any preceding claim, wherein the second heat treatment is carried out as follows: (a) the second maximum temperature is 400°C to 575°C, preferably 450°C to 550°C; and / or (b) maintaining the second coated substrate at the second maximum temperature for at least 30 minutes, preferably 1 hour to 3 hours.
5. A method according to any preceding claim, wherein the carrier substrate is a flow-through substrate.
6. A method according to any preceding claim, wherein the one or more platinum group metal-containing washcoat layers on the carrier substrate comprise Pt and / or Pd.
7. A method according to any preceding claim, wherein the one or more platinum group metal-containing washcoat layers on the carrier substrate further comprise an alkaline earth metal, preferably strontium and / or barium.
8. A method according to any preceding claim, wherein the coated substrate has a continuous platinum group metal-containing coating extending from the inlet end to the outlet end of the carrier substrate.
9. A method according to claim 8, wherein the continuous platinum group metal-containing coating is zoned, wherein an inlet zone comprises Pt and Pd, and whereby an outlet zone comprises Pt and optionally Pd, and wherein: (i) The outlet zone has a smaller Pt loading than the inlet zone, expressed in g / in 3 Count, or (ii) The outlet zone has a greater Pt loading than the inlet zone, expressed in g / in 3 count.
10. The method of claim 9, wherein the continuous platinum group metal-containing coating consists of the inlet zone and the outlet zone.
11. A method according to any preceding claim, wherein step (iv) comprises: (I) applying a washcoat comprising a platinum group metal to said first coated substrate, preferably forming a washcoat zone extending from an inlet end of said substrate; or (II) impregnating the first coated substrate with a solution containing a salt of a platinum group metal, preferably forming a platinum group metal impregnation zone extending from the inlet end of the substrate.
12. A method according to any preceding claim, wherein the heat-treated coated substrate comprises platinum group metal particles having an average particle size (D50) as determined by TEM of greater than 10 nm, preferably greater than 20 nm.
13. A method according to any preceding claim, wherein the diesel oxidation catalyst comprises a layer or zone formed in step (iv) comprising platinum group metal particles, the particles having a D90 particle size as determined by TEM of less than 15 nm, preferably less than 10 nm.
14. A diesel oxidation catalyst article comprising a flow-through carrier substrate having an aged platinum group metal-containing washcoat layer thereon, and a fresh platinum group metal-containing composition deposited on an inlet end thereof, wherein the aged platinum group metal-containing washcoat layer comprises platinum group metal particles having an average particle size (D50) greater than 10 nm as determined by TEM, and wherein the fresh platinum group metal-containing composition comprises platinum group metal particles having a D90 particle size less than 10 nm as determined by TEM.
15. The diesel oxidation catalyst according to claim 14, obtained or obtainable by the method according to any one of claims 1 to 13.
16. An exhaust gas treatment system, comprising a diesel oxidation catalyst according to any one of claims 14 or 15, the diesel oxidation catalyst being arranged upstream of: (A) Soot filter; (B) SCR catalyst products; (C) SCRF catalyst products; (D) catalyzed soot filters; (E) a soot filter followed by an SCR catalyst article; or (F) Catalyzed soot filter followed by SCR catalyst article.
17. A diesel combustion and exhaust treatment system, the diesel combustion and exhaust treatment system comprising: A diesel combustion engine and an exhaust system according to claim 16.
18. A method for manufacturing an exhaust system according to claim 16, the method comprising: A diesel oxidation catalyst is formed according to the method of any one of claims 1 to 13 and arranged upstream of any one of (A) to (F).
Citation Information
Patent Citations
Catalyst with stable nitric oxide (NO) oxidation performance
US20160236178A1
Catalytic articles, systems and methods for the oxidation of nitric oxide
US8679434B1
Monolith coating apparatus and method therefor
WO1999047260A1